Analisis Penggunaan Media Pembelajaran PhET pada Materi Gelombang Berjalan dan Stasioner: A Review Literatur - Lia Koryataini; Maimon Sumo; Lutfiyatul Minnah; Sunariatus Solehah; Anni Rop Atun Khoiroh (PT. PENERBIT TIGA MUTIARA, 2024)
Students can understand and master learning materials if the learning process uses tools and materials called learning media. The tool can be in the form of physical objects, technology or a combination of the two things that are made to communicate information effectively and provide good understanding facilities. Teachers will find it easier to teach when they are able to use learning media as a means when teaching, because the function of learning media is not only as a means of teaching, but also as a way for teachers to make students active and happy to learn. This study aims to describe the use of PhET simulation as a learning medium in traveling and stationary wave theory. This article uses the literature study methodology. The stages in using the literature method include observing, analyzing, then identifying, then providing interpretation, and finally in the form of some evaluation of the research that has been done. There are 25 publication articles obtained from various domestic sources analyzed in this article. The articles used were reported from 2018 to 2024. By using PhET simulation, it feels easier to practice compared to real practicum, because visible media allows users to be more active in presenting subjects that are mastered, especially in traveling and stationary wave material. And by using this PhET virtual media makes students tend to be active and very enthusiastic in the learning process because the appearance of the PhET media is very different from other media. Based on this research, it can be concluded that learning stationary wave and traveling wave material can improve learning outcomes and improve critical thinking skills.